Quantification of gait changes in subjects with visual height intolerance when exposed to heights - Schniepp, Roman; Kugler, Günter; Wuehr, Max; Eckl, Maria; Huppert, Doreen; Huth, Sabrina; Pradhan, Cauchy; Jahn, Klaus; Brandt, Thomas (Frontiers in Human Neuroscience, 2014)
Introduction: Visual height intolerance (vHI) manifests as instability at heights with apprehension of losing balance or falling. We investigated contributions of visual feedback and attention on gait performance of subjects with vHI. Material and Methods: Sixteen subjects with vHI walked over a gait mat (GAITRite®) on a 15-m-high balcony and at ground-level. Subjects walked at different speeds (slow, preferred, fast), during changes of the visual input (gaze straight/ up/ down; eyes open /closed), and while doing a cognitive task. An rmANOVA with the factors “height situation” and “gait condition” was performed. Subjects were also asked to estimate the height of the balcony over ground level. The individual estimates were used for correlations with the gait parameters. Results: Study participants walked slower at heights, with reduced cadence and stride length. The double support phases were increased (all p<0.01), which correlated with the estimated height of the balcony (R2=0.453, p<0.05). ). These changes were still present when walking with upward gaze or closure of the eyes. Under the conditions walking and looking down to the floor of the balcony, during dual-task and fast walking, there were no differences between the gait performance on the balcony and at ground-level. Discussion: The found gait changes are features of a cautious gait control. Internal, cognitive models with anxiety play an important role for vHI; gait was similarly affected when the visual perception of the depth was prevented. . Improvement by dual task at heights may be associated by a reduction of the anxiety level. Conclusion: It is conceivable that mental distraction by dual task or increasing the walking speed might be useful recommendations to reduce the imbalance during locomotion in subjects susceptible to vHI.